Roots and tubers processing in the Caribbean : status and guidelines - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
This publication represents a collaborative effort of several institutions and persons led by the Inter-American Institute for Cooperation on Agriculture (IICA), Trinidad and Tobago Office. The idea for the study of the cassava and sweet potato processors in specific Caribbean countries grew out of an initiative by IICA to direct technical assistance, training and support to operators in selected Caribbean countries - Barbados, Dominica, Guyana, Jamaica, St. Kitts and Nevis, St. Vincent and the Grenadines and Trinidad and Tobago. The idea was shaped into a project proposal by IICA with support from the Caribbean Agricultural Research and Development Institute (CARDI) leading to a project under IICA's Competitive Fund for Technical Cooperation (FonTC).